Before there was Mozart : the story of Joseph Boulogne, Chevalier de Saint-George - Cline-Ransome, Lesa (Schwartz & Wade Books, 2011)
Short biography of Joseph Bologne, Chevalier de Saint-George, a mixed race violinist who would play for the King and Queen of France.